PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA PADA ANAK USIA DINI KELOMPOK B TK KARTIKA VI-15 BIAK - Darlin Darlin; Samar S.; Busyairi Ahmad (Universitas Al-Hikmah Indonesia, 2021)
The implementation of Role PlayingLearning Model to improve the Language Skill of Early Chilhood in Grup B class at KartikaVI-15 Kindergarten Biak. The purpose of the research is to know the improvement of the language skill of early childhood at Kartika VI-15 Kindergarten Biak by conducting the RolePlaying Learning Model. The research method is Classroom Action Research. The data are collected by: (a) observation sheets; (b) interview of early childhood’s language skill; and (c) recording the learning process which is involved the communication the teachers and the learners to know the improvement of early childhood’s language skill. Based on the result of the cycle I, most of the early childhood leaners can already do the activity well, however have not reached the indicator percentage which is 75% that if the early childhood learners reach the score of Growing as Expected and Growing well. While, the result of cycle II evaluation, 95% has been reached by 19 early childhood learners, therefore general the result showed that program of a series impelementation of learning in improving early childhood’s language skill through Role Playing Learning Model in Kartika VI-15 Kindergarten has been completed and achieved the research target which is 75% of success indicator.